2011
DOI: 10.1152/ajpcell.00128.2011
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions favor normal rat kidney epithelial cell adaptation to chronic hypertonicity

Abstract: Upon hypertonic stress most often resulting from high salinity, cells need to balance their osmotic pressure by accumulating neutral osmolytes called compatible osmolytes like betaine, myo-inositol, and taurine. However, the massive uptake of compatible osmolytes is a slow process compared with other defense mechanisms related to oxidative or heat stress. This is especially critical for cycling cells as they have to double their volume while keeping a hospitable intracellular environment for the molecular mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…Osmotic stress increases intracellular macromolecular crowding and leads to the formation of microtubule bundles, as previously reported [55]. In line with this, NaCl treatment indeed leads to the formation of microtubule bundles in control HeLa cells (figure S6A and B).…”
Section: Resultssupporting
confidence: 88%
“…Osmotic stress increases intracellular macromolecular crowding and leads to the formation of microtubule bundles, as previously reported [55]. In line with this, NaCl treatment indeed leads to the formation of microtubule bundles in control HeLa cells (figure S6A and B).…”
Section: Resultssupporting
confidence: 88%
“…Compatible osmolytes can also promote cell survival by SG-independent mechanisms. The recovery of normal cell cytoskeleton after osmotic shock (56,67), such as the MT bundle disassembly observed after betaine accumulation, may play a role in hypertonic adaption. In addition, compatible osmolytes counteract the negative effect of ionic strength regarding protein aggregation (68,69) and have a positive impact on many enzymatic reactions (17) and mRNA translation (19) without considering the DNA-or membranerelated processes.…”
Section: Discussionmentioning
confidence: 99%
“…Compatible osmolytes are small neutral molecules that can be easily exchanged between cells communicating via gap junctions in NRK cells (56). We then explored the idea that cell preconditioning, if monitored by compatible osmolytes, can be transmitted from cell to cell.…”
Section: Cell-cell Interactions Allow Rapid Preconditioning Of Epithementioning
confidence: 99%
“…Given that gap junction plaques are formed in the wounded zone (Spanakis et al , 1998; Desforges et al , 2011) and that migration of polyamine-depleted cells after DFMO treatment is generally impaired, with the inactivation of Rac1 as a possible explanation for this effect (Ray et al , 2003), we explored whether there is a relationship between the variation in polyamine content between quiescent and proliferating cells and the variation in the occurrence of gap junctions in these cells during wound healing. In NRK cells, we observed that confluent quiescent cells did not display gap junction plaques (Figure 8A, right) and the expression of Cx43 was lower than in subconfluent cells (Figure 8B); quantification over three samples indicates that Cx43 expression after glyceraldehyde-3-phosphate dehydrogenase (GAPDH) normalization is reduced about three times (35 ± 10% compared with proliferating cells).…”
Section: Impaired Microtubule Dynamics and Maintenance Of Gap Junctiomentioning
confidence: 99%
“…Indeed, both polyamines (McCormack et al , 1992, 1993; Witte and Barbul, 2003) and gap junction communications (Gabbiani et al , 1978; Goliger and Paul, 1995; Qiu et al , 2003) play a key role during wound healing. In particular, gap junction plaques generally appear in the wounded area, whereas they are barely present away from it (Spanakis et al , 1998; Desforges et al , 2011). Finally, we advance some possible consequences of polyamine-mediated intercellular signalization for normal or abnormal proliferative patterns in vivo, especially during wound healing, tissue regeneration, and cancer and for the global response of epithelia to oxidative stress exposure.…”
Section: Introductionmentioning
confidence: 99%